Analisis Implementasi Kebijakan Pendidikan Pembelajaran Jarak Jauh Pada Masa Pandemi Covid 19 - Akhya Ansori (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2022)
Learning is a core activity in an educational process. Learning can be carried out in class or distance if necessary if there are obstacles to meet in a class due to situations and conditions that do not allow. This study aims to determine (1) the distance learning system that is applied, (2) the impact of the distance learning system on student achievement, (3) the constraints in implementing the distance learning system. The research method used in this study is a qualitative method with a type of descriptive qualitative research approach. The results of this study indicate that the implementation of distance learning still has many obstacles such as inadequate equipment and poor internet connections, besides that the increase in learning success is still small and ineffective.